Frequency of Microorganisms in High Vaginal Swabs Obtained from women in OPD presenting with Vaginal Discharge - Rabeea Sadaf, Nasreen Kishwar, Shazia Tabassum, Bushra Rauf, Sonia Javed, Maira Khan, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: After menstrual irregularities, second common gynecological problem is vaginal discharge. Change in dynamic ecosystem of vaginal flora can cause the overgrowth of pathological microorganism that creates vaginal discharge. Owing to syndromic approach in low income countries, the identification of specific causative organism is masked. Aim: To determine the frequency of various micro-organism in high vaginal swab obtained from women in outpatient department presenting with vaginal discharge. Methodology: We conducted this cross sectional descriptive studybetween January 2022 to December 2022 at Hayatabad Medical Complex, Peshawar. 431 patients were enrolled according to selection criteria. Attending Gynecologist carried out the complete evaluation & established a clinical diagnosis & collected HVS and sent to microbiological laboratory of the institution for reporting. In order to evaluate the participant characteristics and the prevalence of vaginal infections, descriptive statistics were performed. Results: Of the 431 patients who presented with vagina discharge, their high vaginal swabs were sent for culture, 245(57.1%) cases were found positive for pathogens. Among the positive cases, bacterial vaginosis (29.21%) was followed by vaginal candidiasis as the most prevalent microbiological cause of abnormal vaginal discharge (21.2%), trichomonasvaginalis (15.5%) and combined infection (1.63%). Among the positive culture (32.2%) women had normal flora and (43.2%) patients with vaginal discharge had no growth on culture. Practical implication: To detect the most common organism found in vaginal discharge and treat promptly to reduce drugs resistance and prevent complications like chronic pelvic pain preterm labour and infertility. Conclusion: Bacterial vaginosis is the most frequent finding of women presenting with vaginal discharge in Out-Patient Department of our hospital followed be vaginal candidiasis and Trichomonasvaginalis. Keywords: High vaginal swab,Trichomonasvaginalis, Bacterial vaginosis, Vaginal discharge Vaginal candidiasis